Our mission at Mitigate+: Producing evidence to foster low-emission development (video) - CGIAR Initiative on Low-Emission Food Systems (2023)
The Mitigate+: Low-Emission Food Systems Initiative is a ten-year global CGIAR initiative to provide robust, science, data and evidence and test innovative technology development through Living Labs for People to equip government, civil society, private sector and organizations with improved decision-making tools to curb greenhouse gas emissions.